Safety of Delafloxacin: Focus on Adverse Events of Special Interest. (10th September 2018) - Lodise, Thomas; Corey, Ralph; Hooper, David; Cammarata, Sue
Abstract: Background: Fluoroquinolones have been widely used for a variety of Gram-positive and Gram-negative infections, and by 2002 they had become the most commonly prescribed class of antibiotics for adults in the United States. With widespread use, the class has become associated with a range of adverse events. Delafloxacin is a fluoroquinolone approved in the United States for the treatment of adults with acute bacterial skin and skin structure infections (ABSSSIs). Delafloxacin is differentiated from other fluoroquinolones due to structural differences and in its activity against methicillin-resistant Staphylococcus aureus, including quinolone-resistant strains. This paper reviews the safety profile of delafloxacin across clinical studies with an emphasis on the incidence of adverse events of special interest that are associated with fluoroquinolones. Methods: Data from 2 completed phase III studies of delafloxacin for the treatment of ABSSSIs were pooled and are the primary focus of this paper. Additional support from the full safety analysis set (30 completed phase I to phase III clinical studies) is included where applicable. Results: Fewer patients in the pooled delafloxacin group had AESIs than in the comparator group (7.0% vs 9.2%, respectively). Delafloxacin had a low rate of discontinuations due to treatment-related adverse events (<1%). Serious adverse events occurred at similar rates in patients treated with delafloxacin vs comparators. Conclusions: Serious adverse events occurred at similar rates in patients treated with delafloxacin vs nonquinolone comparators used to treat ABSSSIs. Clinicaltrials.gov identifier: NCT01984684 and NCT01811732